Development of integrated intelligent CAD system for synthesis and stress-deformation analysis of pressure vessels - Å ariÄ‡, Isad; MuminoviÄ‡, Adis (International Journal of Engineering and Technology, 2018)
This paper presents the process of developing an integrated intelligent CAD system (IICAD) for synthesis and stress-deformation analysis of pressure vessels. The name of the system is IICAD PP system. The goal of the paper is to present procedures and steps to develop IICAD system for specific type of products. These procedures and steps can be used to develop IICAD system for any type of specific products or family of products. IICAD PP system can help engineers during calculation and design of pressure vessels. The paper shows that IICAD PP system enables quick calculations of design parameters, automatic generations of 3D geometrical model and automatic conduction of numerical analysis for stress and deformation. All these design activities take a lot of time from engineers if they are done using conventional methods.